The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jee.20418
|View full text |Cite
|
Sign up to set email alerts
|

The influence of engineering competition team participation on students' leadership identity development

Abstract: Background: Engineering competition teams (ECTs) allow college students to learn about and practice leadership within a technical domain, yet we know little about the mechanisms by which leadership development occurs within these teams. This paper explores how ECT participation contributes to students' leadership identity development (LID). Purpose: This paper addresses the following research questions: RQ1: How does the ECT experience contribute to students' relational LID? RQ2: What other factors influence E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…The university-business collaborative learning environment proposed has motivating factors common to other studies [54][55][56][57][58][59][60]. As other studies denote [61,62], the inclusion of a real and competitive challenge, posed in collaboration with a business environment, was more effective than working on a fictitious case, and it is an important component of engineering education. The students found that presenting their projects to the rest of the teams, teachers, and professionals of the participating company was satisfying and that their personal relationships increased with your curricular activities.…”
Section: Discussionmentioning
confidence: 97%
“…The university-business collaborative learning environment proposed has motivating factors common to other studies [54][55][56][57][58][59][60]. As other studies denote [61,62], the inclusion of a real and competitive challenge, posed in collaboration with a business environment, was more effective than working on a fictitious case, and it is an important component of engineering education. The students found that presenting their projects to the rest of the teams, teachers, and professionals of the participating company was satisfying and that their personal relationships increased with your curricular activities.…”
Section: Discussionmentioning
confidence: 97%
“…Working in teams gives engineering students an opportunity to practice leadership skills (Knight & Novoselich, 2017; Wolfinbarger & Shehab, 2015), build agency (Liang et al., 2019) and develop a leadership identity (Kwapisz et al., 2019; Rosch & Imoukhuede, 2016; Wolfinbarger et al., 2021). Although many articles in the engineering education literature discuss both leadership and teamwork, the treatment of these concepts is inconsistent.…”
Section: Teamwork and Leadership Development In Engineering Educationmentioning
confidence: 99%
“…Functional leadership theories (Burke et al, 2011) capture many of the activities performed within engineering teams. For example, Wolfinbarger and Shehab (2015) and Wolfinbarger et al (2021) used the team leadership framework (Burke et al, 2006) to identify leadership behaviours reported by members of competition teams. Righter et al (2019) used the functional team leadership model (Morgeson et al, 2010) to categorise leadership behaviours enacted within design teams.…”
Section: Teamwork and Leadership Development In Engineering Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaboration is seen as being crucial in makerspaces because it allows students a significant say in what and how they design and create, allowing them to choose the activity's focus and the dynamics of their group projects (Peppler et al, 2016). Leadership improvement takes place within these teams, even though these teams provide a specialized place to learning about and exercising leadership within a technical domain (Wolfinbarger et al, 2021). Universities are convinced that having a sufficient level of education and training requires students to completely acquire the abilities needed to access the labour market as well as a certain mastery of the subject matter of a particular syllabus (Garcia, 2016).…”
Section: Introductionmentioning
confidence: 99%